2020
DOI: 10.1111/jcmm.16111
|View full text |Cite
|
Sign up to set email alerts
|

Procyanidin B2 improves endothelial progenitor cell function and promotes wound healing in diabetic mice via activating Nrf2

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 49 publications
(123 reference statements)
0
28
0
Order By: Relevance
“…hyperglycemia. Hyperglycemia has been shown to delay diabetic wound healing by inducing dysfunction in the vascular endothelial cells (Fan et al, 2021). Therefore, the improvement of glucolipid metabolism disorders is one of the most effective strategies for the treatment of diabetes and related complications.…”
Section: Discussionmentioning
confidence: 99%
“…hyperglycemia. Hyperglycemia has been shown to delay diabetic wound healing by inducing dysfunction in the vascular endothelial cells (Fan et al, 2021). Therefore, the improvement of glucolipid metabolism disorders is one of the most effective strategies for the treatment of diabetes and related complications.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate effects of EMPA on oxidative stress in heart tissues and PA-treated H9C2 cells, dihydroethidium (DHE) (Molecular Probes, Eugene, OR, USA) superoxide anion fluorescent probe staining was performed to evaluate the oxidative stress level of frozen heart sections and H9C2 cells, as described in our previous research [ 26 ]. Briefly, frozen heart sections of the left ventricle were incubated with 5 ÎŒ M DHE in a dark and humidified container at 37°C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Nrf2 activation in fibroblasts is also induced by many natural compounds including polyphenols, such as curcumin, epigallocatechin-3-gallate (EGCG) or apomorphine, and flavone derivatives as well as many bioactive components of pepper beetle, brassica plants and walnut sprouts extracts [ 120 ]. Similarly, procyanidin B2, one of the major bioactive components of procyanidins promotes wound healing in diabetic mice in a Nrf2-dependent manner [ 86 ]. Curcumin, a potent Nrf2 activator, accelerated the cutaneous wound healing in streptozotocin-induced diabetic rat model [ 121 ].…”
Section: Nrf2 Induction Of Cytoprotective Genes and Nrf2 Dependent Therapeutic Regimens In Wound Healingmentioning
confidence: 99%
“…Schmidt et al showed that cold plasma promotes Nrf2-and p53-mediated granulation and reepithelization in the skin of SKH1 mice. Levels of proinflammatory cytokines IL-6 or TNFα and angiogenetic factors such as FGF, KGF, VEGF and COX2 increase in the early stages [86] in vitro in vivo Cutaneous wound i.p. injection (10 mm dorsal skin) siKeap1…”
Section: The Role Of Nrf2 In Cell Proliferation Apoptosis and Migration During Wound Repairmentioning
confidence: 99%